Raman monitoring laser-induced phase transformation in microcrystalline silicon thin films prepared by PECVD - Concari, Sonia Beatriz (2003)
The results of a study of phase transformation in hydrogenated microcrystalline silicon thin films prepared from hydrogen-diluted silane and exposed to an Ar+ laser light are presented. Through Raman spectroscopy, it was determined that the induced phase transformation is interrelated with silane dilution in hydrogen used as a reactive gas in the preparation of the films and, therefore, depends on the grain size and crystalline fraction of the material. Dark conductivity, transmission electronic microscopy (TEM) and atomic-force microscopy (AFM) data have been used to corroborate the Raman measurements. The results show that the sequence of phase transformation in microcrystalline thin films presents different characteristics from those, which are produced in single-crystal silicon structures. The occurrence of a Raman peak at 350 cm?1 is attributed to the formation of the Si-XII phase. A thermal model to explain the phase transformation is proposed. To our knowledge, neither the presence of the phase Si-XII nor the phase transformation process in microcrystalline silicon thin films has been reported before.